Child abuse : patterns of physical and sexual child abuse presenting at Karl Bremer Hospital and the knowledge and perceptions of the Ravensmead Community on child abuse - Wicomb, Lynne (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MMed)--Stellenbosch University, 2015.